Nausicaa of the Valley of the Wind - Miyazaki, Hayao, 1941-; Shimamoto, Sumi, 1954-; Tsujimura, Mahito; Lohman, Alison, 1979-; Stewart, Patrick, 1940-; Miyazaki, Hayao, 1941- (Los Angeles, CA Shout! Factory, 2017)
Set far in the future on a dying earth, princess Nausicaa of the Valley of the Wind attempts to create peace between her father's kingdom and another fighting for natural resources.
Originally released as a motion picture in 1984.
Based on the manga by Hayao Miyazaki.
DTS-HD Master Audio 2.0, wide screen 1.85:1.
Bonus DVD includes standard definition version of film.
Features: feature-length storyboards, original theatrical trailers, TV spots, audio commentary with Hideaki Anno and Katayama, interview with Toshio Suzuki and Hideaki Anno : Nausicaa and Evangelion! The whereabouts of the giant warrior?, Behind the microphone : join the filmmakers and cast behind the English-dubbed version of the film for an inside look at its creation, Creating Nausicaa.
Japanese voices: Sumi Shimamoto, Mahito Tsujimura, Hisako Kyoda ; English voices: Alison Lohman, Patrick Stewart, Uma Thurman, Shia LaBeouf, Chris Sarandon, Edward James Olmos.
Keywords: Miyazaki, Hayao, -- 1941- -- Film adaptations; Natural resources -- Drama; Drama; Fantasy films; Feature films; Fiction films; Film adaptations; Video recordings for the hearing impaired